2022
DOI: 10.3390/ijms23042264
|View full text |Cite
|
Sign up to set email alerts
|

Antibody-Drug Conjugate Targeting c-Kit for the Treatment of Small Cell Lung Cancer

Abstract: Lung cancer is the leading cause of cancer-related deaths. Small cell lung cancer (SCLC) accounts for 15–25% of all lung cancers. It exhibits a rapid doubling time and a high degree of invasiveness. Additionally, overexpression of c-Kit occurs in 70% of SCLC patients. In this study, we evaluated an antibody-drug conjugate (ADC) that targets c-Kit, which is a potential therapeutic agent for SCLC. First, we generated and characterized 4C9, a fully human antibody that targets c-Kit and specifically binds to SCLC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 49 publications
0
23
0
Order By: Relevance
“…The conjugation of DM1 to c12G1 increased the absorbance at 252 nm ( Figure 4 B). The drug-to-antibody ratio (DAR) was determined as described previously [ 32 ] and found to be approximately 5.07. Since the target-binding affinity of ADC can be reduced by a conformational change via conjugation of the N-hydroxysuccinimide ester of the smcc linker with the primary amines of lysine in the antibody, we compared the binding affinity of 12G1 antibody and 12G1 ADC.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The conjugation of DM1 to c12G1 increased the absorbance at 252 nm ( Figure 4 B). The drug-to-antibody ratio (DAR) was determined as described previously [ 32 ] and found to be approximately 5.07. Since the target-binding affinity of ADC can be reduced by a conformational change via conjugation of the N-hydroxysuccinimide ester of the smcc linker with the primary amines of lysine in the antibody, we compared the binding affinity of 12G1 antibody and 12G1 ADC.…”
Section: Resultsmentioning
confidence: 99%
“…The c12G1 was subcloned into the pCHO 1.0 vector (Thermo Fisher Scientific, Waltham, MA, USA) and the recombinant plasmids were transiently transfected into CHO-S cells (Thermo Fisher Scientific) using OptiPRO™ SFM and FreeStyle™ MAX Reagent (both from Thermo Fisher Scientific), according to the manufacturer’s instructions. The antibody was purified using Protein A Sepharose and SP Sepharose columns (Invitrogen, Waltham, MA, USA), as described previously [ 32 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have demonstrated that 2G4 antibody, a fully human antibody, could inhibit the activation of SCF/c-Kit signaling in various cancer cell lines [ 34 , 35 ]. In addition, another anti-c-Kit antibody 4C9 significantly reduced the expression of c-Kit [ 36 ]. Both 2G4 and 4C9 antibodies could bind to human c-Kit with high binding affinity ( K D of 2G4 = 2.83 × 10 −12 M and K D of 4C9 = 5.58 × 10 −9 M) [ 34 , 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, another anti-c-Kit antibody 4C9 significantly reduced the expression of c-Kit [ 36 ]. Both 2G4 and 4C9 antibodies could bind to human c-Kit with high binding affinity ( K D of 2G4 = 2.83 × 10 −12 M and K D of 4C9 = 5.58 × 10 −9 M) [ 34 , 36 ]. In this study, we investigated whether 2G4 and 4C9 could inhibit the proliferation and degranulation in LAD2, a human mast cell line.…”
Section: Introductionmentioning
confidence: 99%